Heart rate monitoring during combat sports matches: a brief review - Slimani, M.; Znazen, H.; Sellami, M.; Davis, P. (International Journal of Performance Analysis in Sport, 2018)
The aims of the present short review were to (i) summarise data relating to the heart rate (HR) response to combat sports matches according to many factors and (ii) determine the cardiovascular demand and intensity of combat sports matches. The present review shows that HR increased significantly across rounds during male taekwondo, boxing and kickboxing matches. HR and maximal heart rate (HRmax) increased significantly across successive karate and judo combat matches in young men and boy athletes. It has also been shown that there are no significant differences between winners and losers and males and females in HR response during official and simulated striking combat sports matches. Furthermore, combat HR intensity as a percentage of HRmax varied from 90% to 94%, from 86% to 100%, from 83% to 94%, and approximately 95% during judo, taekwondo, karate and Muay Thai matches, respectively. Coaches, sports scientists and athletes can also use HR to (i) assess athletes` cardiovascular demand and (ii) monitor exercise intensity during combat sports matches.